Nonlinear effects in WDM Networks - GAIZI, Kenza; Dr. Fouad Mohammed ABBOU, Pr; Dr. Farid ABDI, Pr (International Journal of Engineering and Technology, 2018)
This paper studies nonlinear effects in WDM Network. The focus is on both the propagation of a unique signal as well as a set of them in optical fibers in a WDM network. The paper presents an analytical model to study the effects of having nonlinearities in a WDM system. Three main nonlinear effects are studied here are Cross Phase Modulation, Self-Phase Modulation, and Four Wave Mixing. Simulations are performed on up to 265 channels WDM System.Â Â